2012
DOI: 10.1093/chemse/bjs076
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Changes in Electrogustometry Thresholds, Tongue Tip Vascularization, Density, and Form of the Fungiform Papillae in Humans

Abstract: The aim of the study was to investigate age-related changes in electrogustometry (EGM) thresholds, in morphology and density of the fungiform papillae (fPap) and in vessels' shape and density at the tip of the human tongue.In 156 nonsmokers (74 males, 82 females; age range: 10-80 years), divided in age groups, EGM thresholds at the chorda tympani area, at the soft palate area, and at the area of the vallate papillae were recorded bilaterally. Morphology and density of the fPap and blood vessels' density and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 14 publications
6
64
2
5
Order By: Relevance
“…Histological observation demonstrated that the mean density of the taste buds of younger subjects was significantly higher than that of elderly subjects. 9 Pavlidis et al 10 reported that aging was associated with a progressive increase in electrogustometry thresholds, and densities of both fPap and vessels decreased significantly in older subjects compared with those of younger subjects. Loss of selectivity in human olfactory sensory neurons with developing age was also observed.…”
Section: Introductionmentioning
confidence: 99%
“…Histological observation demonstrated that the mean density of the taste buds of younger subjects was significantly higher than that of elderly subjects. 9 Pavlidis et al 10 reported that aging was associated with a progressive increase in electrogustometry thresholds, and densities of both fPap and vessels decreased significantly in older subjects compared with those of younger subjects. Loss of selectivity in human olfactory sensory neurons with developing age was also observed.…”
Section: Introductionmentioning
confidence: 99%
“…The mean FP density value reported for elderly individuals was similar to that one in our study. Moreover, ageing was also significantly associated Influencing the taste function in elderly subjects, all these factors were suggested to be relevant (Pavlidis et al, 2012).…”
Section: Resultsmentioning
confidence: 98%
“…Some studies have not reported either significant association or gender differences (Zuniga et al 1993;Just et al, 2006;Zhang et al 2008), but others have done (Segovia et al 2002;Pavlidis et al 2012;Correa et al 2013;Fischer et al 2013). …”
Section: Original Papermentioning
confidence: 99%
“…A further criterion was an absence of recent hospitalizations or severe medical histories such as epilepsy, retinopathy, nephropathy, polyneuropathy, macroangiopathy, hepatitis, cardiac murmurs, radiation therapy of the head and neck, and chemotherapy . Excluding potential participants older than 60 years minimized potential confounding of age on our hypothesized association between diagnosis, gustatory function, and morphology …”
Section: Methodsmentioning
confidence: 99%
“…It produces low‐amplitude stimuli of a predetermined duration (0.5, 1, 1.5, and 2 seconds). A feedback circuit controls the output current with an error quote of <1% …”
Section: Methodsmentioning
confidence: 99%